2000
DOI: 10.1177/172460080001500413
|View full text |Cite
|
Sign up to set email alerts
|

Human MUC1 Mucin: A Multifaceted Glycoprotein

Abstract: Human MUC1 mucin, a membrane-bound glycoprotein, is a major component of the ductal cell surface of normal glandular cells. MUC1 is overexpressed and aberrantly glycosylated in carcinoma cells. The role MUC1 plays in cancer progression represents two sides of one coin: on the one hand, loss of polarity and overexpression of MUC1 in cancer cells interferes with cell adhesion and shields the tumor cell from immune recognition by the cellular arm of the immune system, thus favoring metastases; on the other hand, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 110 publications
1
68
0
2
Order By: Relevance
“…Furthermore, formation and deposition of MUC1-anti-MUC1 circulating immune complexes can result in severe end-organ damage. These shortcomings likely contributed to the limited success of antitandem repeat MUC1 antibodies in clinical trials to date (28,(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, formation and deposition of MUC1-anti-MUC1 circulating immune complexes can result in severe end-organ damage. These shortcomings likely contributed to the limited success of antitandem repeat MUC1 antibodies in clinical trials to date (28,(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-associated MUC1 has been extensively studied as a tumor marker and as a target in cancer therapeutics (28)(29)(30)(31)(32)(33). In an attempt to target MUC1, a variety of anti-MUC1 antibodies have been generated, almost all of which react with epitopes contained within the highly immunogenic tandem 20-amino acid repeat sequence of the MUC1 a chain.…”
Section: Discussionmentioning
confidence: 99%
“…It is expressed in secretory epithelial cells of the airways, GI tract, and female reproductive tract and is associated with goblet cells (124). Its function is not well defined yet, but it appears to play a role in antiadhesion of tumor cells or bacteria (124,125). It can mediate signal transduction responses through Ras, β-catenin, and p53.…”
Section: Regulation Of Other Mucin Genes In the Lungsmentioning
confidence: 99%
“…An interesting example of this is the membrane-bound glycoprotein MUC1 mucin, which is expressed widely on the epithelial surface of glandular cells. 12 An abnormally glycosylated form of MUC1 is expressed on cells during inflammation, on pre-malignant lesions and on carcinoma cells. 13 Furthermore it has been shown that the presence of antibodies to the abnormal MUC1 following mumps infection is associated with a reduced incidence of ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%